Reliability of field-based fitness tests in youth - Artero, E. G.; Espana-Romero, V.; Castro-Pinero, J.; Ortega, F. B.; Suni, J.; Castillo Garzon, M. J.; Ruiz, J. R. (International Journal of Sports Medicine, 2011)
The objective of this systematic review was to study the reliability of the existing field-based fitness tests intended for use with children and adolescents. The medical electronic databases MEDLINE, SCOPUS and SPORTS DISCUS were screened for papers published from January 1990 to December 2009. Each study was classified as high, low or very low quality according to the description of the participants, the time interval between measurements, the description of the results and the appropriateness of statistics. 3 levels of evidence were constructed according to the number of studies and the consistency of the findings. 32 studies were finally included in the present review. The reliability of tests assessing cardiorespiratory fitness (9 studies), musculoskeletal fitness (12 studies), motor fitness (3 studies), and body composition (10 studies) was investigated. Although some fitness components warrant further investigation, this review provides an evidence-based proposal for most reliable field-based fitness tests for use with children and adolescents: 20-m shuttle run test to measure cardiorespiratory fitness; handgrip strength and standing broad jump tests to measure musculoskeletal fitness; 4×10 m shuttle run test for motor fitness; and height, weight, BMI, skinfolds, circumferences and percentage body fat estimated from skinfold thickness to measure body composition.